The locomotor musculature and posture of the early dinosauriform Silesaurus opolensis provides a new look into the evolution of Dinosauromorpha - Piechowski, Rafał (J Anat, 2020)
It is widely accepted that ornithodirans (bird lineage) and some pseudosuchians (crocodilian lineage) achieved fully erect limb posture in different ways. Ornithodirans have buttress‐erected hindlimbs, while some advanced pseudosuchians have pillar‐erected hindlimbs. Analysis of the musculoskeletal apparatus of the early dinosauriform Silesaurus opolensis challenges this view. This ornithodiran had pillar‐erected hindlimbs like some pseudosuchians. This condition could be autapomorphic or represents a transitional state between adductor‐controlled limb posture of early dinosauromorphs and the buttress‐erected hindlimbs of dinosaurs. This sequence of changes is supported by Triassic tracks left by animals of the dinosaurian lineage. It was associated with the strong development of knee flexors and extensors. Furthermore, the forelimbs of Silesaurus were fully erect, analogously to those of early sauropods. Members of both lineages reduced the muscles related to the protraction, retraction and bending of the limb. They used forelimbs more as a body support and less for propulsion. A similar scapula and humerus construction can be found in the Lagerpetidae and Lewisuchus, suggesting that long, slender, fully erected forelimbs are primitive for all Dinosauromorpha, not just Silesauridae. Early dinosaurs redeveloped several muscle attachments on the forelimb, probably in relation to bipedality.